2011
DOI: 10.2341/10-404-l
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Time and Cement Type on Push-Out Bond Strength of Fiber Posts to Root Dentin

Abstract: A self-adhesive resin cement can provide a significantly stronger bond than a three-step etch-and-rinse adhesive and resin cement when used to lute fiber posts. SUMMARYThe bond strength of fiber posts luted with resin cements was evaluated after two storage times in different regions of a post space. A total of 40 single-rooted human teeth were endodontically treated and prepared for cementation of fiber posts (White Post DC). In groups 1 and 3 (G1 and G3, respectively), posts were luted with RelyX ARC, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
2
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 30 publications
3
13
2
7
Order By: Relevance
“…The high BS values observed for U100 in this study and in others 1,[7][8][9]28,[35][36][37] can be attributed to the chemical interaction between monomer acidic phosphate groups and dentin/enamel hydroxyapatite 17 and to low shrinkage of the material, 38,39 leading to closer contact of the resin cement with the root canal walls and higher frictional resistance. 40,41 Unfortunately, there is no consensus in the literature with regard to the superiority of this material when compared with conventional bonding strategies.…”
Section: Discussionsupporting
confidence: 52%
“…The high BS values observed for U100 in this study and in others 1,[7][8][9]28,[35][36][37] can be attributed to the chemical interaction between monomer acidic phosphate groups and dentin/enamel hydroxyapatite 17 and to low shrinkage of the material, 38,39 leading to closer contact of the resin cement with the root canal walls and higher frictional resistance. 40,41 Unfortunately, there is no consensus in the literature with regard to the superiority of this material when compared with conventional bonding strategies.…”
Section: Discussionsupporting
confidence: 52%
“…Then, according to our results, the cervical third had higher bond strength values than the middle third, when compared to resin cements. These results differ from previous studies (17,23) that there were no differences among to the thirds. The differences may result from the comparative analysis between the cervical and middle third, since the apical third was not included in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…The literature presents conflicting results concerning the efficacy of self-adhesive cements versus conventional dual-polymerized ones [6,8,[12][13][14]. However, in general, using an etch-and-rinse approach for conditioning the intraradicular dentin presented better results for both selfadhesive [6,8,[12][13][14] and conventional resins [5,9,10,16,17], while in some studies no significant difference was found between them [6,17]. It has to ne noted that these studies evaluated bond strength results only 24 h after cementation and/or following some type of aging at the bonded interface such as water storage or thermo and/or mechanical cycling.…”
Section: Discussionmentioning
confidence: 99%
“…It has to ne noted that these studies evaluated bond strength results only 24 h after cementation and/or following some type of aging at the bonded interface such as water storage or thermo and/or mechanical cycling. Moreover, the core build up was not performed prior to the push-out test [5,10,12,14,17] or when core applied no information was provided whether the core was prepared immediately or after some time [6,8,13]. Previous studies suggest that clinical procedures such as occlusal adjustment or core preparation prior to complete setting time of the resin cement (24 h) could generate stress at the resin cement interfaces, reducing bond strength results [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation